Major and minor criteria for gastric dystemperaments in Persian Medicine: Sari gastric dystemperament criteria-I (SGDC-I) - Mahshid Chaichi-Raghimi; Reza Ilkhani; Elham Parsa; Mahmood Khodadoost; Rasool Choopani; Roshanak Mokaberinejad; Mojgan Tansaz; Mina Movahhed; Hasan Namdar; Elham Emaratkar; Mahdi Alizadeh-Vaghasloo; Mamak Hashemi; et al. (Babol University of Medical Sciences, 2022)
Background: Gastric disorders are one of the most common human ailments, which impose a huge economic burden on countries. In Persian Medicine (PM), it is possible to predict the susceptibility to gastric diseases with diagnosis of gastric Mizajes (temperaments) and dystemperaments. The semiology of gastric dystemperaments has been investigated in PM textbooks, although the value of each sign and symptom is not mentioned. Consequently, this research is designed to determine the major and minor criteria for classifying gastric dystemperaments on the basis of valid manuscripts and with the help of PM specialists in the present era. Methods: This was a consensus-based study consisting of four phases. In the first phase, reference PM textbooks were studied. Symptoms and signs of gastric dystemperaments were collected and listed in four groups. In the second phase, semi-structured interviews with a sample of PM experts were carried out. Phase three included a focused group discussion with experts. Eventually, findings were integrated from the three study phases in a two-day meeting in Sari City. Results: Selected criteria included eight major and eight minor criteria for hot-cold dystemperament, as well as six major and eight minor criteria for wet-dry gastric dystemperament. Conclusion: Modern lifestyles and the interfering factors are responsible for some changes in diagnostic signs and symptoms according to PM. This was the first step to coordinate PM diagnostic criteria for gastric dystemperaments. Further studies are recommended to reach a unique protocol in the field of PM diagnostics. The next step includes design and validation of national diagnostic tools.